Acute periodontal lesions. (June 2014) - Herrera, David; Alonso, Bettina; de Arriba, Lorenzo; Santa Cruz, Isabel; Serrano, Cristina; Sanz, Mariano
Abstract: This review provides updates on acute conditions affecting the periodontal tissues, including abscesses in the periodontium, necrotizing periodontal diseases and other acute conditions that cause gingival lesions with acute presentation, such as infectious processes not associated with oral bacterial biofilms, mucocutaneous disorders and traumatic and allergic lesions. A periodontal abscess is clinically important because it is a relatively frequent dental emergency, it can compromise the periodontal prognosis of the affected tooth and bacteria within the abscess can spread and cause infections in other body sites. Different types of abscesses have been identified, mainly classified by their etiology, and there are clear differences between those affecting a pre‐existing periodontal pocket and those affecting healthy sites. Therapy for this acute condition consists of drainage and tissue debridement, while an evaluation of the need for systemic antimicrobial therapy will be made for each case, based on local and systemic factors. The definitive treatment of the pre‐existing condition should be accomplished after the acute phase is controlled. Necrotizing periodontal diseases present three typical clinical features: papilla necrosis, gingival bleeding and pain. Although the prevalence of these diseases is not high, their importance is clear because they represent the most severe conditions associated with the dental biofilm, with very rapid tissue destruction. In addition to bacteria, the etiology of necrotizing periodontal disease includes numerous factors that alter the host response and predispose to these diseases, namely HIV infection, malnutrition, stress or tobacco smoking. The treatment consists of superficial debridement, careful mechanical oral hygiene, rinsing with chlorhexidine and daily re‐evaluation. Systemic antimicrobials may be used adjunctively in severe cases or in nonresponding conditions, being the first option metronidazole. Once the acute disease is under control, definitive treatment should be provided, including appropriate therapy for the pre‐existing gingivitis or periodontitis. Among other acute conditions affecting the periodontal tissues, but not caused by the microorganisms present in oral biofilms, infectious diseases, mucocutaneous diseases and traumatic or allergic lesions can be listed. In most cases, the gingival involvement is not severe; however, these conditions are common and may prompt an emergency dental visit. These conditions may have the appearance of an erythematous lesion, which is sometimes erosive. Erosive lesions may be the direct result of trauma or a consequence of the breaking of vesicles and bullae. A proper differential diagnosis is important for adequate management of the case.